THE POLITENESS PRINCIPLE COMPLIANCE USED IN RIDWAN KAMIL'S TWITTER MOURNING TWEETS - Salsabila Ababiel; Yulianto Sabat; Henry Rio (IKIP Siliwangi, 2023)
This research aims to determine the maxims of politeness in Ridwan Kamil’s Twitter tweets in May to June 2022, during which he was dealing with the tragedy that befell his son. The analysis was conducted by employing Leech’s maxim. This research makes a dual contribution, namely a theoretical contribution in the form of futher insights intro how pragmatic theory perceives readers’ linguistic politeness, and a practical contribution in the form of readers’ trained and developed linguistic politeness in everday communicative activities, either directly or through social media. In addition, this research can also contribute to instilling a polite, courteous, and well-spoken character in readers. This research used the descriptive qualitative method. The data collection method used is that the researchers determines Ridwan Kamil’s tweet’s for the last 2 months from May to June 2022 related to the mourning period, reads and observes Ridwan Kamil’s Twitter repeatedly, takes screenshots, and records on the data sheet of Ridwan Kami’s tweets. The results of this research indicated that Ridwan Kamil’s tweets from May to June 2022 comply with the Indonesian maxim of politeness. In this research, no maxims of agreement and maxims of tact were found. Neither no impoliteness or violation of maxims was found in Ridwan Kamil’s Twitter tweets in May to June 2022 during the mourning period. It can be seen that Ridwan Kamil comply the maxim of modesty a lot. This is because during the mourning period Ridwan Kamil was very grateful to all those who prayed for his late son.